2017
DOI: 10.1155/2017/6138145
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Selectins and PSGL-1 as a Key Component in Thrombus Formation and Cancer Progression

Abstract: Cellular interaction is inevitable in the pathomechanism of human disease. Formation of heterotypic cellular aggregates, between distinct cells of hematopoietic and nonhematopoietic origin, may be involved in events leading to inflammation and the complex process of cancer progression. Among adhesion receptors, the family of selectins with their ligands have been considered as one of the major contributors to cell-cell interactions. Consequently, the inhibition of the interplay between selectins and their liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 152 publications
(173 reference statements)
1
54
0
Order By: Relevance
“…97 Platelets induce NETosis by releasing thromboxane A2; then, in turn, NETosis leads to thrombin generation. 37,98 Lymphocytes, monocytes, and neutrophils can also release mtDNA strands. 93 In the blood, mtDNA can be present in both particle-associated and non-particle associated forms.…”
Section: Introductionmentioning
confidence: 99%
“…97 Platelets induce NETosis by releasing thromboxane A2; then, in turn, NETosis leads to thrombin generation. 37,98 Lymphocytes, monocytes, and neutrophils can also release mtDNA strands. 93 In the blood, mtDNA can be present in both particle-associated and non-particle associated forms.…”
Section: Introductionmentioning
confidence: 99%
“…In Sudan, no previous study bound thrombotic pregnant women with PSGL-1 levels or gene polymorphism in patients compared with normal pregnant women that we have done in this study although many studies suggest that there is a strong relationship between PSGL-1 levels and their genetic polymorphisms and thrombosis [18]. A study done by Kappelmayer and Nagy suggests that PSGL-1 and other selectin ligands represent diagnostic biomarkers and ideal targets for the intervention of thrombosis and cancer [22]. Recently, many studies have demonstrated the functional relevance of PSGL-1 polymorphism and different forms of cardiovascular diseases [23], and this indicates that the P-selectin/ PSGL polymorphism may be important in initiating thrombosis in pregnant women and suggests that detection of P-selectin/PSGL polymorphisms in those categories should be made to avoid pregnancy complications.…”
Section: Discussionmentioning
confidence: 76%
“…P-selectin and E-selectin play a vital role in human implantation [349]. PSGL-1 is now known as a major participant in inflammation, thrombus, along with cancer [350]. Due to their role in cancer immune system modulation they are being studied as possible targets for controlling tumor immunity [351].…”
Section: Selectinsmentioning
confidence: 99%